Medium-term economic strategy paper 1996-2000 (Govt. of Antigua and Barbuda [St. John's]AG, 1996)
Sets out the policies and programmes which Government is committed to, and expects to enhance the pace of recovery of the economy from recent hurricane damage, improve the publc sector finances, reform the public service, generate adequate fiscal surplus to expand the pace of public investment in social and economic infrastructure, improve the creditworthiness of Government of Antigua and Barbuda, and facilitate renewed access to perferential financial support from the international donor and lender community.
DC